PERAN MAHASISWA DALAM MENINGKATKAN PEMBERDAYAAN LINGKUNGAN DAN SOSIAL MASYARAKAT DI DESA HAKATUTOBU KEC. POMALAA KAB. KOLAKA - Ray Suryadi; Yuni Cahyani Awe; Sekar Sari; Nurhaifa, Nurhaifa; Anandha Permatasari; Aqli Assaad; Nurkinan, Nurkinan; Dian Armiati; Mala, Mala; Riska, Riska; Fadillah Ramdani; Bernat Julfikli Kalawawo (Bajang Institute, 2024)
This community service activity was carried out in Hakatutobu Village, Pomalaa Subdistrict, Kolaka Regency. The program aimed to raise social and environmental awareness among the community through four main activities: Stop Bullying awareness, Ecobrick, elderly health check-ups, and the provision of trash bins. Each program was implemented using a participatory approach, actively involving the community. The results showed an increase in public awareness regarding cleanliness, plastic waste reduction, elderly health improvement, and bullying prevention in schools. This program is expected to continue and provide long-term benefits to the village community